2002
DOI: 10.1001/archpedi.156.1.55
|View full text |Cite
|
Sign up to set email alerts
|

Role Models, Ethnic Identity, and Health-Risk Behaviors in Urban Adolescents

Abstract: Role model selection is associated with protective psychosocial characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
92
2
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(110 citation statements)
references
References 35 publications
8
92
2
3
Order By: Relevance
“…This study also extends on findings investigating the effectiveness of role model influence in the domains of academics (Lockwood, 2006;Zirkel, 2002;Marx & Roman, 2002;McIntyre et al, 2005;McIntyre et al, 2003), psychological well-being (Yancey et al, 2009;Ziegler & Stoeger, 2008), but especially health (Lankford et al, 2003;.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…This study also extends on findings investigating the effectiveness of role model influence in the domains of academics (Lockwood, 2006;Zirkel, 2002;Marx & Roman, 2002;McIntyre et al, 2005;McIntyre et al, 2003), psychological well-being (Yancey et al, 2009;Ziegler & Stoeger, 2008), but especially health (Lankford et al, 2003;.…”
Section: Discussionsupporting
confidence: 75%
“…Research indicates that role models can motivate individuals to strive for academic and occupational success (Lockwood, 2006;Zirkel, 2002), increase self-esteem and self-efficacy (Yancey, Siegel, & McDaniel, 2009;Ziegler & Stoeger, 2008), and boost performance on a cognitive task by alleviating the adverse effects of stereotype threat (Marx and Roman, 2002;McIntyre et al, 2005;McIntyre, Paulson, & Lord, 2003). Most importantly, role models have also been used effectively to increase behavioral intentions in activities related to improving health (Lankford et al, 2003;Lockwood, Chasteen, & Wong, 2005;Lockwood, Wong, McShane, & Dolderman, 2005).…”
Section: Social Influence and Role Modelsmentioning
confidence: 99%
“…A role model is someone who is admired and seen as an example to be emulated. The positive associations of having a role model include better academic achievement, positive development and well-being, reduced likelihood of risky health behaviors, and greater likelihood of positive health behaviors (DuBois & Silverthorn, 2005;Mistry, McCarthy, Yancey, Lu, & Patel, 2009;Strunin et al, 2015;Yancey, Grant, Kurosky, Kravitz-Wirtz, & Mistry, 2011;Yancey, Siegel, & McDaniel, 2002). In addition, a handful of studies have found that having a role model is specifically associated with greater levels of physical activity among youth (DuBois & Silverthorn, 2005;Mistry et al, 2009;Yancey et al, 2011).…”
mentioning
confidence: 99%
“…Furthermore, program leaders may have served as positive role models for the participants. Previous studies have shown that a strong positive relationship exists between adolescents having an adult role model and reduction of risky behaviors, higher self-esteem, and higher grades (Beier, Rosenfeld, Spitalny, Zansky, & Bontempo, 2000;Yancey, Siegel, & McDaniel, 2002).…”
Section: Strengths and Limitationsmentioning
confidence: 96%